Genome-Wide Identification and In-silico Expression Analysis of Serine Carboxypeptidase-Like (SCPL) Proteins in Soybean (Glycine max L.) (Plant Tissue Culture and Biotechnology, 2025)
The serine carboxypeptidase-like (SCPL) protein family is crucial in plant development and stress response regulation. However, information on SCPL proteins in soybean remains limited. Here, we identified 84 GmSCPL genes distributed across 19 chromosomes. Phylogenetic analysis grouped GmSCPLs into three clusters, closely related to SCPLs in Arabidopsis thaliana and Oryza sativa. Duplication analysis revealed 31 duplicated gene pairs, with 27 linked to whole-genome or segmental duplication and 4 to tandem duplication. Three hub genes, GmSCPL82, GmSCPL46, and GmSCPL16 were identified through protein-protein interaction analysis. Promoter regions predominantly contain cis-regulatory elements for light, hormone, environmental, and growth responses. RNA-seq data highlighted GmSCPL20, GmSCPL33, and GmSCPL76 as highly up-regulated under heat stress; GmSCPL40, GmSCPL64, and GmSCPL69 under drought; and GmSCPL2, GmSCPL27, and GmSCPL37 under salt stress. This study conducted a comprehensive analysis of the SCPL protein family in soybeans, offering a valuable foundation for future research on the role of SCPL genes in abiotic stress tolerance.Plant Tissue Cult. & Biotech. 34(2): 217-235, 2024 (December)